Evaluation of Hematological Changes in Donors Post Apheresis: An Institutional Study - Subhashis Das; Nikhil; Gaurav Khichariya; T. Amrutha; Snigdha Sinha (New Advances in Medicine and Medical Science Vol. 1, 2023)
The aim of the study was to evaluate the haematological changes that transpired post plateletpheresis in apheresis donor and compare pre and postdonation haematological changes in donors and to determine the consequences of apheresis, plateletpheresis on donor’s health. The productivity, quality of platelet apheresis collection has improved because of the considerable advancement in the automated cell separators. This is an observational cross-sectional study done in laboratory at RL Jalappa Blood Bank, Tamaka, Kolar, Karnataka, India. The study was done from March 2019 to August 2020. A total of 300 healthy donors (plateletpheresis donors) were included in the study. All donors underwent plateletpheresis (Haemonetics MCS), and pre- and post-donation haematological parameters including haemoglobin concentration, haematocrit (Hct), platelet, white, and red blood cell counts were computed. Postdonation haematological parameters such as platelet count, haemoglobin, haematocrit, White Blood Cells (WBC), Red Blood Cells (RBC) counts of the donor was noted and it was compared with pre-donation haematological parameters. Statistical analysis was accomplished utilising statistical software SPSS version 16.0. Platelet count, haemoglobin, WBC count, RBC count and haematocrit were noted down from 262 donors and substantially significant reduction was observed in these parameters postdonation. Donor parameter platelet count (lac/mL) value was reduced from 273.57- 224.28 whereas WBC count (cu/mm) predonation value decreased from 9.91-8.86 Postdonation, haemoglobin (g/dL) value decreased from 14.46-12.91, haematocrit (%) decreased slightly from 45.19- 44.19, RBC count (million/mm3) decreased from 5.21-5.01. So it is concluded that values were decreased postdonation. Platelets transfusion can be done either for a remedial or prophylactic cause. Most of the transfusions are given to prevent bleeding in thrombocytopenic patients. Current research carried out demonstrated SDP is efficacious in of thrombocytopenia therapy and it is safe from recipient’s perspective. Technical personnel training, procedures carried out under the supervision of transfusion medicine specialists, and close monitoring of these donors are required to prevent adverse events for the donors’ well-being.